2018
DOI: 10.2306/scienceasia1513-1874.2018.44.257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrient content and antioxidant, neuritogenic, and neuroprotective activities of upland rice bran oil

Abstract: Upland rice bran is an abundant and valuable antioxidant by-product of rice milling. This study compares the content of γ-oryzanol, γ-tocopherol, and phytochemicals in rice bran oil from 4 varieties of upland rice; Dok-kham (DK), Dok-kha (D), Khem-ngen (KN), and Nang-dam (ND); with that of a conventional variety, Khao Dowk Mali 105 (MA). The extraction was done by shaking rice bran in ethanol in 250 ml flask with a rice bran to a solvent ratio of 1:5 (w/v) at 200 rpm (0.447g) and 30°C in the dark for 30 min. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This confirms the findings of Min et al [38], who found no association between rice bran color and natural vitamin E analogue or γ-oryzanol. However, a positive correlation has been reported between γ-oryzanol content and the yellow parameter in upland rice bran oil [39]. Another report noted that rice coproduct oils produced from colored rice contained higher concentrations of oryzanol and phytosterols than noncolored rice [36].…”
Section: Correlationmentioning
confidence: 99%
“…This confirms the findings of Min et al [38], who found no association between rice bran color and natural vitamin E analogue or γ-oryzanol. However, a positive correlation has been reported between γ-oryzanol content and the yellow parameter in upland rice bran oil [39]. Another report noted that rice coproduct oils produced from colored rice contained higher concentrations of oryzanol and phytosterols than noncolored rice [36].…”
Section: Correlationmentioning
confidence: 99%
“…Antioxidant activity in fenugreek seed was greatly improved by roasting at 130 °C for 7 min (38). Antioxidant capacity in the unpolished grain of nonpigmented rice was increased by roasting at 60 °C for 3 min (45). The most suitable roasting temperature and duration for achieving the highest total phenol content and antioxidant capacity was 100 °C in 20 min for pigmented rice and 200 °C for 20 min for nonpigmented rice (31).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, microwave roasting decreased total phenolic content in barley flour resulting in the degradation of antioxidant activity and DNA damage (Baba et al, 2016). A study in rice bran oil has reported an improvement in nutritional value for γ-oryzanol and DPPH antioxidant capacity when unpolished grain of non-pigmented rice was roasted at 60°C for 3 min (Ruen-ngam et al, 2018). On the other hand, as roasting temperature and time increased, rice powder had lower contents of free amino acids (Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%